PREMIUM RISIKO SISTEMATIS INVESTASI JALAN TOL KUNCIRAN-CENGKARENG BERBASIS MODEL STOKASTIK MENGGUNAKAN CAPITAL ASSET PRICING MODEL - Mohamad Agus Setiawan (Jurnal Transportasi, 2009)
The decision for investing in toll road industry requires an acurate feasibility study, because this invesmentinvolves high capical outlays, long term pay-back period, and vulnerability to risk and uncertainty. This studyis conducted using stochastic method which is able to accomodate uncertain variables for calculating InternalRate of Return. Those variables are traffic increment rate, inflation rate, and loan interest rate. To obtain arisk premium used as reference for project feasibility, the Capical Asset Pricing Model (CAPM), wasselected to be utilized in this study. For this case study, it is found that premium risk is 1,35%, consisting ofpremium risk for traffic increment rate 0,88%, inflation rate 0,33%, and loan interest rate 0,14%.Key words: premium risk, Capital Asset Pricing Model, toll road investment, and stochastic method.